A platform for discovering and sharing confidential ballistic crime data. (12th December 2011) - Yates, Simeon J.; Akhgar, Babak; Bates, Christopher; Jopek, Lucasz; Wilson, Richard
Criminal investigations generate large volumes of complex data that detectives have to analyse and understand. This data tend to be 'siloed' within individual jurisdictions and re-using it in other investigations can be difficult. Investigations into trans-national crimes are hampered by the problem of discovering relevant data held by agencies in other countries and of sharing those data. Gun-crimes are one major type of incident that showcases this: guns are easily moved across borders and used in multiple crimes but finding that a weapon was used elsewhere in Europe is difficult. In this paper we report on the Odyssey Project, an EU-funded initiative to mine, manipulate and share data about weapons and crimes. The project demonstrates the automatic combining of data from disparate repositories for cross-correlation and automated analysis. The data arrive from different cultural/domains with multiple reference models using real-time data feeds and historical databases.